Talleres psicopedagógicos para concientizar las situaciones de riesgo en adolescentes del Colegio de Bachillerato “Politécnica de Chimborazo” Riobamba, Comunidad Tunshi. - Zumba Guerra, María Julieta (2023)
Adolescents, from an emotional and psychological viewpoint, go through several risky situations. These problematic situations explain the need to develop skills that help adolescents raise awareness of the possible effects on their health. This study aimed to create Psychopedagogical Workshops to raise awareness of risky situations in adolescents attending Politécnica de Chimborazo High School in Tunshi rural community-Riobamba. For this study, the researcher used a quasi-experimental methodology. As for research tools, teachers took a survey related to the topic. According to teachers, results suggested that the highest risk in students was alcoholism. Therefore, the researcher applied an attitude pretest regarding alcohol consumption. Results revealed that 40% of respondents have a nonfavorable attitude, 34% have an undecided attitude, 16% have a favorable attitude, and 10% have a very optimistic attitude. Based on the results, the researcher planned three psychopedagogical workshops called "Alchohol as an Enemy," "Unmasking the Enemy," and "Living Life without Alcohol." In the workshops, the presenters worked on the conceptualization and basis of alcoholism through different methods and strategies. The workshops emphasized the importance of creating awareness in adolescents. After the posttest, the post-test was applied. Results showed an increase in students' non-favorable attitudes towards alcohol by up to 62%. In sum, we conclude that the workshops had the expected impact on adolescents prone to alcohol consumption and awareness of the damage it causes to their health.